Peningkatan Keterampilan Menyimak Siswa Kelas V SD Negeri 238 Palembang Melalui Model Paired Storytelling Dengan Menggunakan Media Audio Visual - Umar Effendi; Asnimar Asnimar; Bunda Harini; Nuraini Usman; Dedy Hardiansyah (Prodi PGSD FIP UNM, 2018)
The objective of this research is to improve listening skills of students state elementary school 238 Palembang grade V through Paired Storytelling model using audio visual media. The method used in this research is qualitative in the form of action research. The subjects of this study are all students of class Va State Elementary School 238 Palembang which amounted to 34. This research is collaborative, so that researchers and teachers of the class can collaborate. The data were collected by using learning result test and performance test of listening skill. Therefore, this research instrument is a matter and rubric performance appraisal skill listening. This action research is conducted in a cycle that each cycle consists of four stages of planning, action implementation, observation, and reflection. Each cycle in this study consists of two meetings. Based on the data on the average score of listening skills, it is known that an increase from 57.5 in cycle I to 74.5 in cycle II. Therefore, this study ends in cycle II. Based on the results of research and data analysis concluded that the application of audio visual media can improve the listening skills of students of Va Class SD Negeri 238 Palembang through Paired Storytelling model.